Assessing the Prevalence of Publication Misconduct among Iranian Authors Using a Double List Experiment - Maryam HADJI; Fariba ASGHARI; Masoud YUNESIAN; Payam KABIRI; Akbar FOTOUHI (Tehran University of Medical Sciences, 2016)
Background: This study was done to determine the prevalence of publication misconduct among Iranian authors. Methods: Data were collected through an email survey of corresponding authors of papers published in Iranian journals indexed in Scopus during 2009-2011. Using the double list experiment, these individuals were indirectly questioned about committing one of the five misconducts including duplicate publication, falsification, guest authorship, plagiarism, and fabrication over the past year. Results: The survey was sent to 2321 individuals; 100 emails bounced, and of the remaining, 813 (36.60%) people responded to the questions. The prevalence rates were 4.15% for fabrication, 4.90% for plagiarism, 18.10% for guest authorship, 12.65% for falsification of the study methods, and -5.40% for duplicate publication. Among respondent 56.50% trusted the method and confidentiality of the survey and 6.50% did not trust the method or confidentiality at all. Conclusion: We found that the double list experiment method is simple and reliable for use in the academic community, and it can be conducted easily in an e-survey. According to our results, the most common misconducts among Iranian authors are guest authorship and falsification of the methodology. In light of the negative and maleficent impact of publication misconduct in the scientific society, we recommend raising awareness and educating authors and investigators in this regard. To determine the accuracy of the method used in this study, further studies on publication misconduct using a control group and direct questioning, as well as other indirect methods are suggested.